Food-induced immunoglobulin E-mediated allergic rhinitis. Issue 2 (June 2016) - Al-Rabia, Mohammed W.
Abstract: Food allergies are estimated about 1–2% in adults and 8% in children younger than 6 years. Allergic rhinitis is a common disease with a prevalence of 40% among different societies. Although, some foods play a role on exacerbation of allergic rhinitis symptoms, but still there are controversies about the role of diet on incidence or worsening the symptoms. The ongoing research demonstrates a possible relationship between certain foods and their induction of allergic reactions by modulating immunoglobulin E. A total of 100 patients (including both children and adults), between the ages 10 to 60 years, diagnosed with allergic rhinitis were selected for the study. Pregnant females and treated patients with antihistamine were excluded from the study. In vitro serum immunoglobulin E (IgE) levels mediated by a combination of food and inhalant allergens were detected by RIDA ® Allergy Screen in blood samples. Data were presented as mean, standard deviation and standard error. A statistical analysis was performed by one-way analysis of variance (ANOVA). A p value < 0.05 was considered statistically significant. We reported that 63% of patients with allergic rhinitis were sensitized to common food allergens whereas the rest 37% of patients were not sensitive to any of the food allergens. Similarly, a correlation between the age groups of patients with allergic rhinitis and food allergy were also accomplished. We found the highest response rate for allergic rhinitis and food allergy (53.2%) for the people between aged between 21 years and 40 years. We also demonstrated that females are more prone to mediate allergic rhinitis as induced by food allergies as compare to males (i.e., 66.2% vs. 33.3%). Food allergy is estimated to be 4.5% in adolescents and adults with asthma, rhinitis or both. Rice, citrus fruits, black grams and banana are identified as major allergens for inducing allergic-rhinitis symptoms.